Prevalence of depression among clients with diabetes and hypertension in selected hospital at Mangaluru, India - Bizo Vadeo; Sukesh Shetty; M Nalini (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Non-communicable diseases are lifestyle diseases that are increasing throughout the world. They are responsible for 71% of death worldwide, among which 16 million people die prematurely or before reaching the age of 70 years. Among the non-communicable diseases, diabetes and hypertension are the most common. The study aimed to find the prevalence of depression among diabetes and hypertensive clients. MATERIALS AND METHODS: A descriptive cross-sectional study was conducted among 370 subjects diagnosed with diabetes mellitus, hypertension, and both in Justice K.S Hegde Charitable Hospital at Mangaluru. A purposive sampling technique was adopted to select the subjects. Patient health questionnaire-9 (PHQ-9) was used to find the depressive symptoms among the client. The statistical analysis was conducted using SPSS version 20 (Armonk, NY: IBM Corp.); descriptive (frequency and percentage) and inferential (one-way analysis of variance (ANOVA)) statistics were used to interpret the data. RESULTS: Out of 370 subjects, 41% had no depression, and most 59% had mild to severe levels of depression. Among clients diagnosed with diabetes mellitus (n = 139), the majority (63%) had mild to severe depression. Similarly, of subjects diagnosed with hypertension, 51% had no depression, and 49% had mild to severe depression. In addition, among subjects diagnosed with both diabetes mellitus and hypertension (n = 99), 67% had mild to severe depression. CONCLUSIONS: The study shows that many diabetes and hypertensive patients attending the outpatient departments of the hospital experience depression. So, it is crucial to identify the depressive symptoms early and take appropriate measures to prevent complications.